The effectiveness of progressive muscle relaxation on anxiety in adolescents who experience internet addiction (HEALTH CARE: JURNAL KESEHATAN, 2025)
Excessive internet use has an impact especially on mental health conditions, one of which is anxiety. Young people have a more emotional relationship with social media, feel anxious when they can't be online, and have difficulty relaxing at bedtime. Internet addiction and anxiety are two problems that can influence each other. Internet addiction can often cause or weaken anxiety, while anxiety can weaken internet addictive behavior. Progressive muscle relaxation techniques are one method that can help overcome anxiety. The aim of the research is to identify the effectiveness of progressive muscle relaxation on anxiety in internet addiction at SMPN 4 Tarogong Kidul, Garut Regency. This research method uses a quasi-experimental design with a non-equivalent control group design with pre-test and post-test. Sampling used non-probability sampling, consecutive sampling of 30 people. The results of the research show that the p value is 0.00 (